Empirically informed ethics: morality between facts and norms - van Schaik, Carel; Fischer, Johannes; Huppenbauer, Markus; Tanner, Carmen; Christen, Markus (Library of Ethics and Applied Philosophy, 2014)
This volume provides an overview of the most recent developments in empirical investigations of morality and assesses their impact and importance for ethical thinking. It involves contributions of scholars both from philosophy, theology and empirical sciences with firm standings in their own disciplines, but an inclination to step across borders-in particular the one between the world of facts and the world of norms. Human morality is complex, and probably even messy-and this clean distinction becomes blurred whenever one looks more closely at the various components that enable and influence our moral actions and ethical orientations. In that way, morality may indeed be located between facts and norms-and an empirically informed ethics that is less concerned with analytical purity but immerses into this moral complexity may be an important step to make the contributions of ethics to this world more valuable and relevant.